Single-SectionFabry-Perot Mode-Locked Semiconductor Lasers. (27th January 2011) - Yang, Weiguo
Abstract : We present a review of the theoretical models and experimental verification of the single-section Fabry-Perot mode-locked semiconductor lasers based on multiple-spatial-mode (MSM) coupling. The mode-locked operation at the repetition rates of 40 GHz and higher and the pulse width of a few picoseconds are confirmed by the intensity autocorrelation, the fast photo detection and RF spectrum, and the optical spectral interference measurement of ultrafast pulse. The spatial mode coupling theory of single-section Fabry-Perot mode-locked semiconductor lasers is also reviewed, and the results are compared with the experimental observations. The small signal modulation response of these lasers, which exhibits high-frequency responses well beyond the relaxation oscillation resonance limit, is also modeled theoretically, and the simulation is verified by the experimental measurements.